First-Line Osimertinib in Patients with EGFR-Mutant Advanced Non-Small Cell Lung Cancer: Outcome and Safety in the Real World: FLOWER Study. (23rd August 2021) - Lorenzi, Martina; Ferro, Alessandra; Cecere, Fabiana; Scattolin, Daniela; Del Conte, Alessandro; Follador, Alessandro; Pilotto, Sara; Polo, Valentina; Santarpia, Mariacarmela; Chiari, Rita; Pavan, Alberto; Dal Maso, Alessandro; et al.
Abstract: Background: Osimertinib became the standard treatment for patients with untreated EGFR -mutant advanced non-small cell lung cancer (aNSCLC) following results reported in the phase III randomized FLAURA trial. Because of strict exclusion criteria, patient populations included in pivotal trials are only partially representative of real-world patients. Methods: We designed an observational, prospective, multicenter study enrolling patients with EGFR -mutant aNSCLC receiving first-line osimertinib to evaluate effectiveness, safety, and progression patterns in the real-world. Results: At data cutoff, 126 White patients from nine oncology centers were included. At diagnosis, 16 patients (12.7%) had a performance status (PS) ≥2 and 38 (30.2%) had brain metastases. Overall response rate (ORR) was 73%, disease control rate (DCR) 96.0%. After a median follow-up of 12.3 months, median time to treatment discontinuation (mTTD) was 25.3 months, median progression-free-survival (mPFS) was 18.9 months and median overall survival (mOS) was not reached (NR). One hundred and ten patients (87%) experienced adverse events (AEs), 42 (33%) of grade 3–4, with venous thromboembolism (VTE) as the most common ( n = 10, 7.9%). No difference in rates of VTE was reported according to age, PS, comorbidity, and tumor load. We observed longer mTTD in patients without symptoms (NR vs. 18.8 months) and with fewer than three metastatic sites at diagnosis (NR vs. 21.4 months). Patients without brain metastases experienced longer mPFS (NR vs. 13.3 months). No difference in survival outcome was observed according to age, comorbidity, and type of EGFR mutation. Isolated progression and progression in fewer than three sites were associated with longer time to treatment discontinuation (TTD). Conclusion: Osimertinib confirmed effectiveness and safety in the real world, although thromboembolism was more frequent than previously reported. Abstract : The FLOWER study is an observational prospective multicenter study focusing on outcome, safety, progression pattern, and clinical management of untreated patients with EGFR -mutant advanced non-small cell lung cancer receiving first-line osimertinib in the real world.